Parasitic infections in the organic beef cattle herds of southern Poland during the grazing season, with the first record of Calicophoron daubneyi (Dinnik, 1962) in the country - Nosal Paweł; Kowal Jerzy; Basiaga Marta; Węglarz Andrzej (Journal of Veterinary Research)
Grazing cattle are vulnerable to the harmful effects of gastrointestinal parasites. Organically farmed cattle are even more so because conventional antiparasitic treatments are restricted, yet parasite infection patterns in Polish organic herds remain poorly documented.